Chinese herbal medicine combination therapy for patients with steroid-dependent ulcerative colitis: Study protocol for a systematic review and meta-analysis - Ye, Qiaobo (Medicine (Baltimore), 2020)
BACKGROUND: Ulcerative colitis (UC) is a chronic non-specific intestinal inflammatory disease characterized by continuous and diffuse inflammatory response of colonic mucosa. Steroid-dependent UC is an important type of UC. Chinese herbal medicine is widely used in treating steroid-dependent UC in China. However, there is no systematic review and meta-analysis to collate and evaluate the evidence of these studies. The purpose of this research is to provide evidence of the efficacy and safety of Chinese herbal medicine in treating steroid-dependent UC. METHODS AND ANALYSIS: Six databases, including 3 English databases and 3 Chinese databases will be searched. In addition, other grey literatures and ongoing studies will also be searched. Two researchers will independently select eligible studies by reading titles, abstracts and full texts according to the inclusion and exclusion criteria. Risk of bias assessment will be conducted by 2 independent reviewers using Cochrane risk-of-bias tool. The outcomes include steroid-free remission rate, Total clinical effective rate, Incidence of adverse events, Disease activity index (modified Mayo score), Results of enteroscopy (Baron score) and mucosa (geboes index score). Heterogeneity between studies will be assessed by Cochrane X(2) and I(2) tests. We will conduct subgroup analysis and meta-regression to explore the source of heterogeneity. We will also evaluate the stability of the results through sensitivity analysis and publication bias through funnel plot and Egger test. RESULTS: The results will be published in peer-reviewed journals. CONCLUSION: Our meta-analysis and systematic evaluation results will confirm whether Chinese herbal medicine is effective in the treatment of steroid-dependent UC. It will provide more ideas for future research. OSF REGISTRATION NUMBER: DOI: 10.17605/OSF.IO/YP79Z